(untitled) (Journal of Social Sciences Review, 2023)
This quantitative research study investigates the role of marketing ethics in ensuring clients’ satisfaction, with a sample size of 200 participants drawn from a specific population. The primary objective of this research is to examine the relationship between marketing ethics and clients’ satisfaction levels. The study aims to determine whether ethical marketing practices positively influence clients’ perception of an organization and their satisfaction with its products or services. To achieve this objective, a structured questionnaire was developed and administered to the selected sample. The questionnaire includes items that assess participants’ awareness and perception of marketing ethics, as well as their satisfaction levels. The findings of the study were analyzed using statistical techniques, including correlation analysis and regression analysis, to explore the potential relationship between marketing ethics and client satisfaction. The results provided insights into the extent to which ethical marketing practices impact clients’ satisfaction levels. The implications of this research are significant for organizations operating in diverse industries. In conclusion, this quantitative research study aims to fill a gap in the literature by examining the role of marketing ethics in ensuring clients’ satisfaction. The findings provided valuable insights for organizations seeking to align their marketing practices with ethical standards and enhance their relationships with clients.